2006
DOI: 10.2134/agronj2004.0089
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effects of Elevated Carbon Dioxide and Drought on Wheat

Abstract: Atmospheric CO 2 concentration (C a ) continues to rise. An imperative exists, therefore, to elucidate the interactive effects of elevated C a and drought on plant water relations of wheat (Triticum aestivum L.). A spring wheat (cv. Yecora Rojo) crop was exposed to ambient (Control: 370 mmol mol 21 ) and free-air CO 2 enrichment (FACE: ambient 1 180 mmol mol 21 ) under ample (Wet), and reduced (Dry), water supplies (100 and 50% replacement of evapotranspiration, respectively) over a 2-yr study. Our objective w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
66
2
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 84 publications
(132 reference statements)
7
66
2
1
Order By: Relevance
“…For example, heat-induced shortening of the grain-filling stage could limit the benefits from higher CO 2 ; conversely, improved water-use efficiency from higher CO 2 may help to reduce negative impacts of VPD increases or rainfall declines. Decades of plotlevel (Kim et al, 2007;Shimono et al, 2007;Markelz et al, 2011) and open-air field Wall et al, 2006;Zhu et al, 2011) experiments as well as simulation modeling exercises (Long, 1991;Brown and Rosenberg, 1997;Grant et al, 2004) have been dedicated toward understanding the net impact of interactions between competing global change mechanisms at small scales. However, the results have not always been conclusive, especially at regional scales relevant for projecting the future response of overall crop production to changing environmental conditions.…”
Section: Crop Response To Global Change Mechanismsmentioning
confidence: 99%
“…For example, heat-induced shortening of the grain-filling stage could limit the benefits from higher CO 2 ; conversely, improved water-use efficiency from higher CO 2 may help to reduce negative impacts of VPD increases or rainfall declines. Decades of plotlevel (Kim et al, 2007;Shimono et al, 2007;Markelz et al, 2011) and open-air field Wall et al, 2006;Zhu et al, 2011) experiments as well as simulation modeling exercises (Long, 1991;Brown and Rosenberg, 1997;Grant et al, 2004) have been dedicated toward understanding the net impact of interactions between competing global change mechanisms at small scales. However, the results have not always been conclusive, especially at regional scales relevant for projecting the future response of overall crop production to changing environmental conditions.…”
Section: Crop Response To Global Change Mechanismsmentioning
confidence: 99%
“…It would be premature, however, to draw any firm conclusion with respect to the impacts of elevated CO 2 on cyanogenesis in cassava given the limited number of studies. Given that plants grown at elevated CO 2 generally have improved water use efficiency [187,210,211], it is possible that any increase in cyanogens in plants in response to future increases in CO 2 will be countered by improved plant water-status in the field. Again, this is an area we consider significant and further studies should be of high priority.…”
Section: Cassava Production In a High Co 2 Worldmentioning
confidence: 99%
“…As has previously been suggested, increasing [CO 2 ] reduces crop stomatal conductance, decreasing ET and, consequently, conserving soil water. Wall et al (2006) found that in wheat, such a mechanism enhanced yield, growth, and photosynthesis. In fully irrigated crops, however, Ottman et al (2001) did not find such positive effects.…”
Section: Discussionmentioning
confidence: 99%